The role of zakat institutions during Covid-19 pandemic to enhance the well being of asnaf in Malaysia (MAIWP as a case study) - Azmi, Mohammad Shahid; Ahjij, Abdelhafid; Zaib, Adham; Zakariyah, Habeebullah (Usuli Faqih Research Centre, 2024)
A lot of individuals have lost their lives to the recently emerged Covid-19 pandemic. Due to the pervasive dread, it has generated, all activity has ceased, especially in the economic sphere. In 2020, there was a global recession due to the global economic blockade; consequently, it caused people to live under financial constraints, so ISF emphasizes that action is required. Due to the effectiveness of Zakat, it can alleviate economic hardships. This study assessed how Majlis Agama Islam Wilayah Persekutuan (MAIWP) contributed to sustaining the Asnaf community and helped alleviate the hostile impact of the COVID-19 pandemic on the Malaysian people, during and after the extent of pandemic instability. The study applied a qualitative method, drawing on secondary databases. These findings suggest that Islamic Social Finance (ISF) methods, such as Zakat, may provide and distribute financial aid during and after a crisis, such as the Covid-19 pandemic, in disciplines other than medicine. The relevant institutions or bodies must continue to provide an efficient method for Zakat contributors to continue contributing to Zakat, as this facilitates the distribution of suitable funds and the eradication of poverty in crisis-affected communities. Thus, effective methods of distribution area essential for Zakat to achieve its goal of assisting the impoverished